Host government digitalization and Chinese OFDI entry mode choice: green-field investment vs cross-border M&A - Li, Xiaoge; Li, Guangqin; Li, Xin (Technological and Economic Development of Economy, 2025)
Based on a theoretical framework based on the perspectives of open governance, transparent governance, and smart governance, the article comprehensively explains the potential impact of host country government digitalization on Chinese enterprises’ OFDI entry mode selection. The results indicate that host government digitalization significantly promotes the probability of Chinese enterprises investing by greenfield investment mode; After using instrumental variable to eliminate endogenous interference and undergoing a series of robustness checks, this conclusion remains robust; Host government digitalization influences the OFDI mode choices of Chinese enterprises by suppressing corruption and strengthening intellectual property protection. Based on the research conclusions, we put forward policy suggestions on “how Chinese enterprises should make OFDI entry mode decision and optimize the project management after entry based on the level of host government digitalization“. First published online 02 April 2025